Effects of different starch sources in concentrates on meat characteristics, nutrient composition, and collagen solubility of dairy steers - Sahatsanon, K.; Chaosap, C.; Sivapirunthep, P.; Sawanon, S.; Setakul, J.; Sitthigripong, R. (International Journal of Agricultural Technology, 2022)
The influences of three different starch sources in concentrates - ground corn (CO), ground cassava (CA), and pineapple stem starch (PI) formulated as a 40% in concentrate - on meat quality, texture profile, nutrient composition, and collagen solubility of the Longissimus thoracis (LT) of dairy steers were investigated. Meat quality and texture profile did not differ significantly between treatments (P>0.05). Nutrient composition did not differ between treatments except that ash content of PI was higher than the other treatments (P<0.05). Starch sources had no effect on collagen content and solubility in LT muscle. Based on the results of this study, pineapple stem starch can be used as an alternative energy source in concentrates without negative effects on meat characteristics